Use of oral contraceptives in three European countries: a population-based multi-database study. (2nd January 2016) - Bezemer, Irene D.; Verhamme, Katia M. C.; Gini, Rosa; Mosseveld, Mees; Rijnbeek, Peter R.; Trifirò, Gianluca; Sturkenboom, Miriam C. J. M.; Penning-van Beest, Fernie J.A.; Herings, Ron M.C.
ABSTRACT: Objectives : The aim of the study was to assess the prevalence of oral contraceptive (OC) use, user characteristics and prescribing patterns by accessing health care databases of three European countries. Methods : A retrospective study was performed from 2009 to 2010 in three general practice (GP) databases from the Netherlands, UK and Italy and in one database of linked pharmacy and hospitalisation data in the Netherlands. The presence of selected chronic conditions and diagnoses of diseases associated with OC use were assessed, as were switches, discontinuations and types of OC used during the study period. Results : Among 2.16 million women aged 15 to 49 years, 16.0% were using an OC on 1 January 2010. The prevalence ranged from 19.7% in a Dutch database to 2.6% in the Italian database. During 2009 and 2010, mainly second-generation progestogens were prescribed in the Netherlands (79.4% and 78.3% of users), both second- (57.9%) and third-generation progestogens (43.6%) were prescribed in the UK, and mainly third-generation progestogens in Italy (61.8%). Most switches were to third- or fourth-generation pills. The prevalence of chronic diseases tended to be higher among OC users, and the proportions of women with a history of disease associated with OC use tended to be lower than among non-users. Conclusions : Second-generation OCs were most frequently prescribed in the Netherlands. In the UK, and even more so in Italy, many women used third- or fourth-generation OCs. Preparation switches were mainly to third- or fourth-generation OCs. Among OC users, a somewhat higher prevalence of chronic diseases was observed; however, information bias cannot be ruled out. Abstract : 摘 要目的 本研究的目的在于通过分析三个欧洲国家多个卫生数据库，评估口服避孕药的应用率、应用者的特征及处方类型。 方法 本回顾性研究分析了2009年至2010年荷兰、英国与意大利的三个常规实践（GP）数据库，以及荷兰的一个药店连锁数据库与医院数据库。研究评估了某些与口服避孕药相关的慢性情况与疾病诊断，研究期间口服避孕药非连续性应用且种类多样。 结果 研究包含216万名女性，年龄分布在15岁至49岁，其中16.0%的女性在2010年1月1日应用口服避孕药。应用率最高为荷兰数据库（19.7%），最低为意大利数据库（2.6%）。在2009年至2010年期间，荷兰女性主要应用第二代避孕药（分别有79.4%与78.3%的女性），英国女性应用第二代（57.9%）与第三代避孕药（43.6%），意大利女性主要应用第三代避孕药（61.8%）。最多的转换是第三代或第四代避孕药。服用口服避孕药的女性慢性病的发生率有升高的趋势，患有与口服避孕药相关病史的女性比例低于非口服避孕药女性。 结论 二代口服避孕药是荷兰女性最常用的类型。在英国与大部分意大利女性，三代与四代口服避孕药应用更多。准备转换主要为三代与四代口服避孕药。在口服避孕药应用者中，观察发现慢性病的发生率更高，但不排除信息存在偏倚。